A psychometric analysis of the clinical screening scale - Quatrochi, Brunna; dos Santos Amaral, Gabriela; Bazán, Jorge Luis; Pap da Silva, Emanuela (Brazilian Journal of Biometrics, 2025)
A psychometric analysis of the SQR-20 screening scale is proposed, composed of twenty dichotomous items that assess indicators of common mental disorders (CMD). Databases from the years 2021, 2022, and 2023 were used, obtained through questionnaires applied by GAPSI and Apoia USP, answered by undergraduate students from USP São Carlos. The results indicate that the test is reliable and unidimensional, and CMD scores can be obtained both through classical test theory and the two-parameter model of item response theory (IRT). Considering IRT, the results showed that the two-parameter model was the most suitable to represent the responses, highlighting that questions related to feelings of sadness and nervousness are more discriminating than physical questions. More severe items, such as suicidal thoughts, are concerning but less effective for discrimination. The comparative analysis between sociodemographic variables, such as age, gender, and course, revealed a significant impact on the well-being of students. Additionally, the weighting of responses highlighted the importance of the course in determining the difficulties faced by students. With these results, it is expected to propose more effective interventions for promoting mental health and well-being in the academic environment.